PEMETAAN RISIKO BENCANA TANAH LONGSOR SEBAGAI UPAYA MITIGASI DI KOTA PAGAR ALAM - Dinata, Alharia; Dhiniati, Fameira (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2019)
The practice of land-use change that occurs in the city of Pagar Alam is an impact of economic growth. Its existence located at an altitude of 315.9 - 3150.9 masl and the type of wet-very wet climate is a driving factor for the occurrence of landslides so that it can harm the material and even fatalities. The purpose of this study is to analyze the distribution of hazards, vulnerabilities, capacities, and risks of landslides. The research method used is a quantitative survey and descriptive analysis using a GIS approach. The results of overlaying parameters according to their respective weights show that, the percentage of landslide hazard distribution with index 0-0.33 covering 289.25 km2 (46%), index 0.34-0.66 covering 243.25 km2 (38%), and index 0.67-1 covering 100.72 km2 (16%). Vulnerability index from 0.67 to 0.68 as many as 3 districts administered and index from 0.59 to 0.68 as many as 32 districts administered. While the index capacity of 0.33 is 16 districts administered and 19 districts administered have a capacity index of 0.67. The percentage of moderate landslide disaster risk distribution is 10% and 90% with a high-risk class.